ECONOMIC EFFICIENCY OF INVESTMENTS IN VINEYARD PRODUCTION IN RISKY CIRCUMSTANCES - Gogić, Petar (Economics of Agriculture, 2018)
Risk management is one of very important problems concerning investment analysis, because it is impossible to predict future events with certainty at the moment when investment decision has been made. It is especially typical for agricultural production which is significantly influenced by naturals factors. Such factors may cause various risks, thus it is necessary to pay special attention to investment evaluation in risky circumstances. Probability estimation for some future events depends on quality of available data, professional experience and applied methodology. Having that in mind, the goal of this paper is to comprehend possible risks in vineyard production and ways to deal with the risks. Moreover, objective of the paper is to analyze economic effectiveness of investments (using adequate methodology) as well as to make choice between different vineyard planting models in risky circumstances. Data needed for formation of investment models originate from concrete investment vineyard planting project as well as comprehensive professional literature on vineyard planting projecting.